Stress fractures - Hough, D. O.; Ray, R. (1994)
1. Stress fractures occur in all age groups and all sports where repetitive activity is performed, but female athletes suffering from amenorrhea are at especially high risk for developing stress fractures, particularly if their diets are low in calcium. 2. The diagnosis of stress fractures is highly dependent on the clinician's ability to assess common signs and symptoms and to correctly interpret various types of radiologic evidence. Symptoms of stress fractures are similar to those of other types of injuries, but stress fractures can be diagnosed very accurately by the use of radionuclide bone scans. 3. Rehabilitation of stress fractures usually requires 3-8 weeks of relative rest combined with cross-training techniques that focus on improving flexibility and strength, plus a gradual return to a specifically prescribed full training program. Therapy with nonsteroidal anti-inflammatory drugs and application of ice treatments and other physical modalities are commonly included as part of the rehabilitation process. 4. To ascertain the progress of rehabilitation, regular biomechanical evaluations of the athlete should be administered to observe the degree to which movement patterns used remain abnormal and/or are likely to result in reinjury. 5. Many stress fractures are preventable. Proper conditioning and preseason training are essential; proper equipment and footwear along with well-designed training programs that gradually increase the frequency and intensity of exercise are additional important factors in prevention.